The long march : building an Afghan National Army - Younossi, Obaid (Rand Corporation monograph series ;, 2009)
The Afghan National Army (ANA) is critical to the success of the allied efforts in Afghanistan and the ultimate stability of the national government. This monograph assesses the ANA's progress in the areas of recruitment, training, facilities, and operational capability. It draws on a variety of sources: in-country interviews with U.S., NATO, and Afghan officials; data provided by the U.S. Army; open-source literature; and a series of public opinion surveys conducted in Afghanistan over the past several years. Although the ANA has come a long way since the outset of the recent conflict in the country, the authors conclude that coalition forces, especially those of the United States, will play a crucial role in Afghanistan for the foreseeable future, particularly in light of the increased threat from Taliban forces and other illegally armed criminal groups.